Practice of continuing care with Traditional Chinese Medicine nursing for patients after surgical treatment of mixed hemorrhoids in the specialized outpatient clinic (基于专病门诊的混合痔术后患者延续性中医护理实践) - Qin Shasha (秦沙沙); E Haiyan (鄂海燕); WEI Yongchun (魏永春); PENG Yujie (彭雨洁); TANG Ling (唐玲); LI Ye (李野); WANG Yali (王亚丽); DONG Yuxia (董玉霞) (中西医结合护理)
Objective To investigate the practice effect of continuing care with Traditional Chinese Medicine nursing for patients after surgical treatment of mixed hemorrhoids in the specialized outpatient clinic. Methods Totally 80 patients undergoing surgical treatment of mixed hemorrhoids of Damp-Heat type were randomly divided into the observation group and the control group, with 40 cases in each group. All patients received routine perioperative nursing during hospitalization. Patients in the control group received routing telephone follow-up and health education after discharged form hospital, and those in the observation group were given continuing care with Traditional Chinese Medicine nursing in the specialized outpatient clinic, and a three-step integrated management of follow-up was carried out. The occurrence of postoperative complications was assessed, and patient satisfaction was evaluated by using a self-made questionnaire. Results The score of postoperative complication evaluation in the observation group was lower than that in the control group (P＜0. 01). The patient satisfaction rate was 97. 50%(39/40), which was higher than 82. 50%(33/40) in the control group (P＜0. 05). Conclusion The practice of continuing care with Traditional Chinese Medicine nursing in the specialized outpatient clinic is potentially effective to reduce the risk of postoperative complications after surgical treatment of mixed hemorrhoids and improve the patient satisfaction. (目的 探讨基于专病门诊的延续性中医护理在混合痔(湿热下注型)术后出院患者中的应用效果。方法 选取2020年4月—12月科室收治的80例混合痔(湿热下注型)术后出院患者为研究对象, 随机分为观察组和对照组, 各40例。两组患者住院期间均接受常规围手术期护理。对照组患者出院后给予电话回访、健康宣教; 观察组患者出院后, 实施基于专病门诊的延续性中医护理方案, 采取“三步护理一体化”的管理模式进行随访管理。对术后两周内并发症情况进行评分, 采用自制问卷调查患者满意度。结果 观察组患者并发症评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组患者满意率97. 50%(39/40), 高于对照组的82. 50%(33/40), 差异有统计学意义(P＜0. 05)。结论 基于专病门诊的延续性中医护理方案能降低混合痔术后患者并发症发生风险, 提高患者满意度。)